Obesity and orthodontic treatment: is there any direct relationship? - Alberto Consolaro
ABSTRACT Obesity is a wide-spread condition directly or indirectly connected with an increase in the prevalence of a variety of human diseases. It affects over 50% of the western overall population. In 2017, a thorough analysis of 204 studies on obesity and cancer revealed that the condition increases the risk of the following types of cancer: stomach, colon, rectal, bile duct, pancreatic, esophagus, breast, endometrial, ovarian, kidney and multiple myeloma. The first study aiming at establishing a connection between obesity and the rate of induced orthodontic tooth movement was conducted by Saloom et al; however, it could not effectively nor significantly reveal any direct influence or effect. Despite being identified during the first week, differences could not be explained and treatment time remained unchanged. In spite of lack of studies in the literature on the connection between obesity and the rate of induced tooth movement, in clinical practice, courses or specialized training, we should not have protocols changed nor adopt any measures or expect significant differences between normal-weight and obese individuals. It should be emphasized that unsuccessful cases or cases of root resorption associated with treatment should not be assigned to obesity, since scientific data is insufficient to do so.